Regularly irregular atrial rhythm after superior vena cava isolation: Another manifestation of sinoatrial node injury?. Issue 1 (2nd November 2021) - Nakashima, Takashi; Nagase, Masaru; Shibahara, Taro; Ono, Daiju; Yamada, Takehiro; Tanabe, Gen; Suzuki, Keita; Yamaura, Makoto; Ido, Takahisa; Takahashi, Shigekiyo; Aoyama, Takuma
Abstract: The present case described an unusual clinical manifestation of the sinoatrial node (or sinoatrial junction) injury during superior vena cava isolation.